DOES FINANCIAL REPORTING REGULATION AFFECT ECONOMIC GROWTH OF THE SIGNATORIES TO THE AfCFTA? (Journal of Global Accounting, 2023)
This work looked at the effect of financial reporting regulation on the economic growth of the 54 signatories to the African Continental Free Trade Area (AfCFTA). Specifically, the study examined the effect of International Financial Reporting Standards (IFRS) adoption on the economic growth of the signatories to the AfCFTA. It used IFRS adoption as proxy for financial reporting regulation and real GDP as proxy for economic growth. Secondary data were collected from the database of IFRS foundation, International Monetary Fund, World Bank and other official documents for the period 2012-2021. Panel data regression was used to analyse the data. Findings show that IFRS adoption has a significant positive effect on the economic growth of the signatories to the AfCFTA. From the results of the analysis, it can be concluded that countries that have fully adopted IFRS experienced faster economic growth than countries that have not.  Based on this conclusion, it is recommended that more emphasis should be placed on financial reporting regulation. Specifically, signatories to the AfCFTA are encouraged to fully adopt IFRS as the financial reporting standard for private organizations, this is because IFRS adoption has been shown to increase the rate of economic growth which will help the countries achieve the objectives of AfCFTA.
Keywords: AfCFTA; Economic growth; IFRS adoption